2012
DOI: 10.1152/jn.00578.2011
|View full text |Cite
|
Sign up to set email alerts
|

Representation of 3-D surface orientation by velocity and disparity gradient cues in area MT

Abstract: Sanada TM, Nguyenkim JD, DeAngelis GC. Representation of 3-D surface orientation by velocity and disparity gradient cues in area MT. J Neurophysiol 107: 2109 -2122, 2012. First published January 4, 2012; doi:10.1152/jn.00578.2011.-Neural coding of the threedimensional (3-D) orientation of planar surface patches may be an important intermediate step in constructing representations of complex 3-D surface structure. Spatial gradients of binocular disparity, image velocity, and texture provide potent cues to the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
(98 reference statements)
1
14
0
Order By: Relevance
“…S4). Given this result, the finding that tilt-selective middle temporal neurons have weak texture sensitivity may, in part, reflect that the stimuli were presented binocularly (10). The present findings are also consistent with the sensation of depth being stronger when a texture stimulus (e.g., a painting with perspective) is viewed monocularly rather than binocularly (22), reflecting the elimination of the cue conflict occurring when pictorial depth cues are viewed binocularly.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…S4). Given this result, the finding that tilt-selective middle temporal neurons have weak texture sensitivity may, in part, reflect that the stimuli were presented binocularly (10). The present findings are also consistent with the sensation of depth being stronger when a texture stimulus (e.g., a painting with perspective) is viewed monocularly rather than binocularly (22), reflecting the elimination of the cue conflict occurring when pictorial depth cues are viewed binocularly.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies examining neuronal sensitivity to 3D orientation cues, either the texture-defined and disparity-defined slants could not be equated (9) or the texture stimuli were only presented binocularly (7,8,10). In contrast, we rendered the stimuli such that the texture-defined and disparity-defined slants were equivalent, and presented texture stimuli monocularly and binocularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pilot work, we observed that local orientation cues in checkerboard stimuli could 10 be used to perform the task without having to judge slant. To avoid this potential confound, the 11 discrimination task was performed using RDS planes with uniform dot density on the screen 12 (Sanada et al, 2012). In CIP, slant tuning curves measured with planar surfaces with a 13 checkerboard pattern or a random dot pattern are highly correlated (Rosenberg and Angelaki, 14 2014b).…”
mentioning
confidence: 99%
“…Numerous psychophysical, computational, and neurophysiological studies have probed the human ability to estimate surface slant, surface tilt, and 3D shape [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Lawful performance has been observed and models have been developed that nicely describe performance.…”
Section: Introductionmentioning
confidence: 99%